The Effect of Capital Adequacy Ratio, Debt Ratio, Credit Risk, Liquidity Risk, and Management Efficiency on Profitability: A Study of the Financial Institutions Sector, Banking Sub-Sector, Listed on the IDX for the 2020–2024 Period - Intan Sari; Supriyono; Hutomo Rusdianto (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
This study investigates the impact of capital adequacy ratio, debt ratio, credit risk, liquidity risk, and management efficiency on the profitability of banking institutions listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Employing a quantitative approach, the research utilizes secondary data from annual financial reports of 47 banks, selected through purposive sampling. Data analysis was conducted using classical assumption tests and multiple linear regression. The results reveal that capital adequacy ratio and debt ratio do not significantly affect profitability, while credit risk and management efficiency have a significant negative effect. Liquidity risk shows a negative but insignificant impact. The findings indicate that effective credit risk management and operational efficiency are crucial for enhancing bank profitability. In conclusion, the simultaneous influence of all five variables explains a substantial portion of profitability variation, highlighting the importance of internal financial management in the banking sector.